Brachydactyly Type A1 Caused by an IHH Variant in a Patient with Disproportionate Short Stature: A Case Report - Inés García de Pablo; María Cristina Ontoria Betancort; Francisco Martínez Bugallo; Sebastián Eustaquio Martín Pérez; Isidro Miguel Martín Pérez (Reports, 2026)
Introduction and Clinical Significance: Skeletal dysplasias comprise a genetically heterogeneous group of disorders with substantial phenotypic overlap, often complicating diagnosis. Clinical exome sequencing (CES) can facilitate molecular diagnosis in children with unexplained disproportionate short stature. Case Presentation: An 8-year-old boy presented with severe short stature (−3.24 SDS), brachydactyly, relative macrocephaly, broad nasal bridge, and mild calf hypertrophy. Endocrine evaluation confirmed growth hormone deficiency (GHD). Following negative SHOX testing, CES identified a heterozygous likely pathogenic IHH variant (c.446G>A; p.Arg149His), establishing the diagnosis of brachydactyly type A1 (BDA1). Recombinant human growth hormone (rhGH), initiated for GHD, resulted in improved growth velocity and height SDS. Transient unilateral prepubertal gynecomastia developed during treatment and resolved after temporary rhGH withdrawal, with no recurrence following reinitiation. Conclusions: This case highlights the diagnostic value of CES in children with disproportionate short stature after unrevealing targeted testing and illustrates that GHD may coexist with IHH-related skeletal dysplasia. An integrated genetic and endocrine evaluation can refine diagnosis, identify coexisting treatable endocrine disorders, and guide individualized management.